Coach-athlete dyad: perception of psychosocial and environmental factors in the relationship - a case study (Pareja entrenador-atleta: percepción de los factores psicosociales y ambientales en la relación – un estudio de caso) - Vigário, Pedro; Teixeira, Armando; Mendes, Felício (Retos, 2020)
Abstract. In this study, we intended to identify psychosocial and environmental factors common to both, coach and athlete, in a situation of relational dyad, perceived by themselves, in a context of individual sport. In the same way, to perceive which factors were considered most preponderant in the sports performance by the two elements of the dyad. Two interviews were conducted individually, to both coach and athlete, and identified the variables present in this dyad by the coding of the interviews. In the analysis of the collected data, the method used was qualitative. Ten common factors were identified: environment, confidence, empathy, mental exigency, motivation, objectives, perfectionism, resilience, overcoming and values. However, there were significant differences in the relative frequencies of each of these factors, depending on whether they came from the coach or the athlete. It was concluded that, despite the existence of factors common to both subjects, the perception of their significance for the relationship, is not the same. The results also suggest that coaches have a significant focus on the variables of competence. On the other hand, the athletes, in addition to the competence variables, also focus on bond factors such as confidence, or self-knowledge factors such as overcoming. Resumen. En este estudio pretendemos identificar factores psicosociales y ambientales comunes a ambos, entrenador y atleta en situación de pareja relacional, percibidos por los propios, en contexto de modalidad individual. De igual modo, percibir cuáles los factores juzgados más preponderantes en el rendimiento deportivo por los dos elementos de la pareja. Fueron realizadas dos entrevistas, individualmente, a ambos, entrenador y atleta, identificadas las variables presentes en esta pareja a través de la codificación de las entrevistas. En el análisis de los datos recogidos, el método utilizado fue cualitativo. Se identificaron diez factores comunes: ambiente, confianza, empatía, exigencia mental, motivación, objetivos, perfeccionismo, resiliencia, superación y valores. Sin embargo, se verificaron diferencias significativas, en cuanto a las frecuencias relativas de cada uno de estos factores, dependiendo se provenían del entrenador o del atleta. Se concluyó que, a pesar de la existencia de factores comunes a ambos sujetos, la percepción de su significancia para la relación no es igual. Los resultados sugieren que los entrenadores tienen un foco significativo en las variables de cualificaciones. Por otro lado, los atletas, más allá de las variables de cualificación, también tienen foco en factores de vínculo como la confianza, o de autoconocimiento, como la superación.